Satisfacción en la Formación Profesional y su Relación con el Rendimiento Académico en los Estudiantes de la Universidad Le Cordon Bleu - Támara T, Stalein (2014)
The next job is to analyze the relationship between training satisfaction levels with Academic Performance in University Students Le Cordon Bleu in 2013. To carry out research a questionnaire to 170 university students from Le Cordon Bleu was validated using Cronbach Alfa indicator with an estimate of 0.80 is acceptable was developed.  Using the Chi Square test showed that there is no relationship between Student Achievement and Vocational Training, where also the satisfaction of infrastructure, teacher attitude and job satisfaction by the administrative staff was measured.